2021
DOI: 10.3390/en14216929
|View full text |Cite
|
Sign up to set email alerts
|

A Staged Approach for Energy Retrofitting an Old Service Building: A Cost-Optimal Assessment

Abstract: Office buildings built before the pre-1960 age constitute a relevant group for analyzing the energy performance of the Portuguese building sector. A dynamic energy simulation was used to assess the energy performance of an existing office building located in the town of Bragança, Portugal. By using a staged renovation approach, two passive technologies applied to the building envelope and an efficient domestic hot water system were selected and a financial evaluation through the net saving (NS) method was unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Discount rate depends on the interest rates set up by national central banks. As a consequence of 365 energy‐efficient measures applied to a public historical building in Turkey and a sensitivity analysis performed to detect the cost optimal energy calculations with considering the inflation rate, different interest rates, and calculation periods demonstrated that a reduction in economic parameters decreased the cost effectiveness in the scenarios having high initial investment costs, while application of two passive technologies to office building located in the town of Bragança, Portugal with using the real discount rates of 3 % and 1 % illustrated that the financial profitability depends on discount rate used in the analysis very much [30, 32].…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Discount rate depends on the interest rates set up by national central banks. As a consequence of 365 energy‐efficient measures applied to a public historical building in Turkey and a sensitivity analysis performed to detect the cost optimal energy calculations with considering the inflation rate, different interest rates, and calculation periods demonstrated that a reduction in economic parameters decreased the cost effectiveness in the scenarios having high initial investment costs, while application of two passive technologies to office building located in the town of Bragança, Portugal with using the real discount rates of 3 % and 1 % illustrated that the financial profitability depends on discount rate used in the analysis very much [30, 32].…”
Section: State Of the Artmentioning
confidence: 99%
“…Two passive technologies namely; internal insulation for roof and vertical envelope applied to the building and an installation of aerothermal heat pump for the domestic hot water system were selected by using a staged renovation approach to assess the energy performance of an existing office building located in the town of Bragança, Portugal and a financial evaluation through the net saving method was made with using the real discount rates of 3 % and 1 % to choose the best efficiency measures for improving the building's energy performance. The results of the study demonstrated that the financial profitability of energy renovation investments was very sensitive to the discount rate employed in the analysis [32].…”
Section: Introductionmentioning
confidence: 97%
“…Payback time, Net Present Value (NPV), and Internal Rate of Return (IRR) are the most common methods used for estimating economic impact of investments from a life cycle perspective [29,[52][53][54][55][56]. Payback time estimates the required time to recover the cost of an investment [56]. On the other hand, NPV determines the present value of all future cash flows, including the investment costs [29,[54][55][56].…”
Section: Perform Trade-off Optimizationmentioning
confidence: 99%
“…Payback time estimates the required time to recover the cost of an investment [56]. On the other hand, NPV determines the present value of all future cash flows, including the investment costs [29,[54][55][56]. Finally, IRR shows the discount (or interest) rate when the NPV is equal to zero, at the end of the assessed time interval [52,53].…”
Section: Perform Trade-off Optimizationmentioning
confidence: 99%
See 1 more Smart Citation